Penerapan Biologi Etika dalam Proses Fermentasi Pembuatan Pupuk Organik Cair Berbahan Dasar Air Kelapa “Cocos nucifera” - Wiwik Romauli Nababan; Maya Febrina Sinaga; Nella Juriska Raja GukGuk; Nurbaity Situmorang; Khairiza Lubis (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study is motivated by the high volume of coconut water (Cocos nucifera) waste that has not been optimally utilized, despite containing natural nutrients such as sugars, minerals, and bioactive compounds with potential as liquid organic fertilizer (LOF) material. This condition leads to environmental problems in the form of organic waste accumulation and the loss of potential economic value from local resources. The aim of this study is to analyze the application of biological ethics in the fermentation process of coconut water-based LOF and its impacts on environmental, economic, and agricultural sustainability aspects. The research employed an experimental approach using anaerobic fermentation assisted by Lactobacillus sp. and Saccharomyces cerevisiae over 14 days. The observed parameters included pH changes and microbial activity during the fermentation process. The results indicated a gradual decrease in pH, reflecting optimal fermentation activity and the formation of organic acids that enhance nutrient availability. From a bioethical perspective, the utilization of coconut water as LOF provides positive impacts, including waste reduction, increased economic value of organic residues, and support for sustainable agriculture practices. In addition, this process encourages community participation in managing local resources in an environmentally responsible manner. Therefore, coconut water-based LOF has the potential to serve as an innovative and sustainable solution for organic farming systems.